4 - Théories, idéologies et stratégies de développement en Afrique: Vers une voie africaine de développement - MARTIN, Guy (Africa Development, 1983)
This paper is an attempt to give some tentative and partial answers to the following two questions: What is the meaning of «development»? What strategy of development for Africa? In trying to answer the first question, we have been led, after the definition of concepts, to question the usefulness of the various existing theories and strategies of develop ment (Capitalism and Socialism) and to explore the true meaning of the concept of «development», which appears as nothing but a myth. In an attempt to answer the second question we have, on the basis of an ope rational definition of «development», delineated the broad outlines of an African strategy of development based on the concepts of social justice, self-reliance, cultural liberation and continental integration. It is to be hoped that other African scholars will pick up the challenge and further contribute to the elaboration of this model so that it can become a useful means towards the global transformations of the African continent. Guy MARTIN, Chargé de cours, Institut des Relations Internationales du Cameroun, Université de Yaoundé, Yaoundé/Cameroun